KINETIKA REAKSI TRANSESTERIFIKASI MINYAK GORENG BEKAS DENGAN KATALIS HETEROGEN CaO DARI CANGKANG KERANG DARAH (Andara granosa) - Midiyarti, -; Nurhayati, -; Muhdarina, - (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
Biodiesel (Fatty Acid Methyl Ester / FAMEs) is an alternative fuel replacing crud oil (petroleum) which is more friendly to environmen, unsmelling and containing no sulfur. Biodiesel is produced by reacting vegetable oil with alcohol using a base as a catalyst. The transesterification has carried out used waste frying oil with CaO catalyst from blood mussel shells (Anadara granosa) that calcined at a temperature of 800oC for 10 hours as heterogeneous base catalyst. The reaction of transesterification produce products that is optimalized by varying the temperature of the reaction time, and determined by the reaction order. The reaction follows first kinetics order with an activation energy (Ea) which is 93.5 kJ / mol and the frequency factor (A) which is 8,16x 1010min-1. The biodiesel Characterization fuel is measured according to ASTM D 6751. The blood mussel shell (Anadara granosa) is a new source for production of heterogeneous base catalysts that can be used for synthesis biodiesel with high purity.